An inductive signalling network regulates mammalian tooth morphogenesis with implications for tooth regeneration. (17th August 2013) - Li, Z.; Yu, M.; Tian, W.
Abstract Sequential and reciprocal epithelial–mesenchymal interactions, essential throughout such aspects of tooth morphogenesis as patterning, size and number of teeth, involves a well‐ordered series of inductive and permissive signals that exert global control over cell proliferation, differentiation and organogenesis. In particular, growth factors, transcription factors and their corresponding receptors, as well as other soluble morphogens, make up a regulatory network at the molecular level that synergistically or antagonistically controls intra‐/inter‐cellular signal transduction during odontogenesis. This review summarizes recent advances in the study of crucial signalling pathways, for example of BMPs, Wnt, Notch, Shh and FGF, with emphasis on the potential integrated signalling network responsible for tooth formation. Our work probes into the complexity of these inductive signalling pathways to promote the understanding of tooth regeneration. Additionally, our study provides further insights into therapeutic strategies for various dental abnormalities in patterning and number, such as tooth agenesis and supernumerary teeth.